Strengthen PSNP Institutions and Resilience Phase II (SPIR II), Ethiopia: Group Problem Management Plus (g-PM+) Pilot, Follow-up 1 - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
IFPRI, in collaboration with World Vision (WV) and implementation partners, evaluated the impact of a psychotherapy intervention, group Problem Management plus (gPM+), with and without a one-time lump sum cash transfer. The study is an interventional study using a cluster randomized control trial (cRCT) design that occurred in 70 kebeles across the regions of Oromia and Amhara. The evaluation includes a screening survey to assess eligible men and women; a baseline survey conducted before implementing the gPM+ or cash transfer intervention (June-July 2022); and two follow up surveys (the first conducted September 2022-October 2022, and the second October 2023-January 2024). This dataset is with respect to the first follow up survey and contains baseline demographic information on the sample in the gPM+ study. The first part comprises of household-level modules such as household roster, housing, assets, consumption, food security, investments, and occurrence of shocking events. The second part is composed of individual-level modules administered to the individuals screened for the study. These modules include instruments for measuring stress, anxiety, coping, self-efficacy, time and risk preference, savings, time use, and childcare.